2013
DOI: 10.1111/inr.12076
|View full text |Cite
|
Sign up to set email alerts
|

Depression, self‐esteem and anger expression patterns of Korean nursing students

Abstract: The development of an anger control programme for nursing students should focus on lowering depression and enhancing self-esteem. One of the policy issues focused on providing anger management programmes for lowering depression and enhancing self-esteem. This study will enable nursing students to recognize the importance of controlling their anger, enhancing their self-esteem, establishing positive emotions and improving their overall well-being as future professional nurses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 10 publications
1
25
0
4
Order By: Relevance
“…The study results showed that the highest score of those for all three anger expression subscales was for anger‐control, indicating that the mean score for anger‐control was above average, while those for anger‐in and anger‐out were below average. Consistent with the findings of a study conducted by Cha & Sok (), nursing students exhibited a tendency towards controlling their anger effectively. However, the scores for anger‐in and anger‐out, considered as dysfunctional anger expression in our study, were higher relative to those observed in Korean homeless men with alcohol problems and difficulty in maintaining stable relationships in another study (Park & Kim ).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The study results showed that the highest score of those for all three anger expression subscales was for anger‐control, indicating that the mean score for anger‐control was above average, while those for anger‐in and anger‐out were below average. Consistent with the findings of a study conducted by Cha & Sok (), nursing students exhibited a tendency towards controlling their anger effectively. However, the scores for anger‐in and anger‐out, considered as dysfunctional anger expression in our study, were higher relative to those observed in Korean homeless men with alcohol problems and difficulty in maintaining stable relationships in another study (Park & Kim ).…”
Section: Discussionsupporting
confidence: 89%
“…Higher scores on the subscales indicate stronger characteristics for each related form of anger expression. In Cha & Sok's () study, Cronbach's alpha coefficients among Korean nursing students were 0.73 for anger‐in, 0.74 for anger‐out and 0.75 for anger‐control. Cronbach's alpha coefficients were 0.77 for anger‐in, 0.73 for anger‐out and 0.79 for anger‐control in the present study.…”
Section: Methodsmentioning
confidence: 92%
See 1 more Smart Citation
“…Estes fatores estressores podem ocasionar desordens psicológicas e físicas (fadiga, ansiedade e cansaço), afetando a vida acadêmica e em consequência o futuro profissional, pois há comprometimento do cotidiano do aluno. Sendo as alterações de saúde: depressão, ansiedade, estresse, aumento do sentimento raiva, angústia, desespero, mau humor, má qualidade do sono, uso de álcool, cansaço e fadiga (11)(12)(13)(14)16,(18)(19)(20)26,28,(29)(30)(31)(32)(33) , descritas como transitórias e de fácil superação pelos estudantes investigados.…”
Section: Resultsunclassified
“…No cenário internacional, entre os estudos envolvendo sintomatologia depressiva em estudantes de enfermagem, pesquisa com 320 estudantes de enfermagem na Coréia mostra que prevalência de depressão pode estar associada a baixa autoestima e a raiva, identificados como preditores para depressão (Cha, Sok, 2014). Por outro lado, pesquisa com 93 estudantes de enfermagem na Espanha mostra que os fatores protetores como a autoestima, tem contribuído para minimizar os efeitos negativos da depressão.…”
unclassified